2016
DOI: 10.1159/000450766
|View full text |Cite
|
Sign up to set email alerts
|

Use of Extended-Release Calcifediol to Treat Secondary Hyperparathyroidism in Stages 3 and 4 Chronic Kidney Disease

Abstract: Background/Aims: Vitamin D insufficiency and secondary hyperparathyroidism (SHPT) are associated with increased morbidity and mortality in chronic kidney disease (CKD) and are poorly addressed by current treatments. The present clinical studies evaluated extended-release (ER) calcifediol, a novel vitamin D prohormone repletion therapy designed to gradually correct low serum total 25-hydroxyvitamin D, improve SHPT control and minimize the induction of CYP24A1 and FGF23. Methods: Two identical multicenter, rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 18 publications
7
84
1
7
Order By: Relevance
“…A cross-sectional study [13] concluded that PTH levels in patients with stages 1-5 CKD progressively declined as serum 25-hydroxyvitamin D increased above 30 ng/mL and that 25-hydroxyvitamin D levels well above 42-48 ng/mL would be required for iPTH normalization in the more advanced CKD. Data from 3 prospective controlled studies [12,14], including the 2 presented herein, support higher serum total 25-hydroxyvitamin D targets in patients with stage 3 or 4 CKD.…”
Section: Discussion/conclusionmentioning
confidence: 54%
See 3 more Smart Citations
“…A cross-sectional study [13] concluded that PTH levels in patients with stages 1-5 CKD progressively declined as serum 25-hydroxyvitamin D increased above 30 ng/mL and that 25-hydroxyvitamin D levels well above 42-48 ng/mL would be required for iPTH normalization in the more advanced CKD. Data from 3 prospective controlled studies [12,14], including the 2 presented herein, support higher serum total 25-hydroxyvitamin D targets in patients with stage 3 or 4 CKD.…”
Section: Discussion/conclusionmentioning
confidence: 54%
“…Exclusion criteria included a spot urine calcium:creatinine (Ca:Cr) ratio of > 0.2, nephrotic range proteinuria (> 3 mg/mg Cr), and a history of parathyroidectomy for SHPT or renal transplantation. Subjects were enrolled progressively from December 2012 to January 2014 at sites of many different latitudes in order to minimize seasonal variation in mean baseline serum total 25-hydroxyvitamin D. Further details regarding these studies have been previously published [14,21].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Renewed interest in this metabolite in the recent years resulted in the FDA approval of extended release (ER) calcifediol in the US in 2016. Studies in patients with CKD stages G3–G4 showed that, unlike the immediate release calcifediol, the ER formulation induces a gradual rise in serum 25(OH)D level along with a significant suppression of PTH levels (at least 30% from baseline), in spite of lower mean calcidiol levels [68]. A slight rise in calcitriol levels (from 34.4 to 46.7 pg/mL), proportional to the rise in calcidiol, was also noted, suggesting that the renal and/or extrarenal CYP27B1 were not downregulated by the rising levels of calcitriol.…”
Section: Future Directionsmentioning
confidence: 99%